Marketing ‘Literary England’ beyond the special interest tourist - Ingram, Claire; Themistocleous, Christos; Rickly, Jillian M.; McCabe, Scott (My University, 2021)
The paper examines the likelihood of mainstream (US general sample) and special interest tourists (literary society members) travelling to English literary tourism destinations. The study applied a mixed methods approach comprising a correlational study of two comparative consumer surveys together with interviews with travel agents. Findings indicate that literary society members have a greater propensity to visit literary tourism destinations. However, they are more likely to visit when familiar with the associated book or film, whereas the general tourist is prepared to visit regardless. Moreover, literary society members profess a greater preference for independent – over organised – travel than mainstream tourists when travelling internationally. This paper thus offers implications for how ‘Literary England’ can be better promoted to different market segments.
Keywords: Literary Tourism; Marketing Tourism; Special Interest Tourist; Destination Marketing